Ethnobotanical survey of medicinal plants in Phulbari Upazila of Dinajpur District, Bangladesh (Bangladesh Journal of Plant Taxonomy, 2006)
Ethnobotanical survey in Phulbari Upazila of Dinajpur district has revealed a total of 86 species used as medicinal plants by the Santal community. Santal names, part/s used as medicine and diseases to be treated with each plant have been presented. A number of threats to medicinal plants and their habitats have been identified and some measures have also been recommended for the conservation of medicinal plants and their habitats in the area. Key words: Ethnobotanical survey, threats and conservation, Bangladesh DOI: 10.3329/bjpt.v13i1.596 Bangladesh J. Plant Taxon. 13(1): 63-68, 2006 (June)